THE ANALYSIS OF PERCEIVED QUALITY AND PERCEIVED VALUE USING IPA ANALYSIS AT VONNTTE BARBERSHOP IN MANADO - Madja, Triwahyudin K.; Tumbuan, Willem J.F.Alfa; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Satisfaction may be defined as a condition when the customers perceive the results from the evaluation of the whole aspects of building a relationship. Perceived quality was defined as consumers? judgment about products? excellence or superiority. Perceived value represents a trade-off between quality or benefit they perceived from the product and the sacrifice they perceive by paying the price. In this globalization era when fashion is important it makes human also like to be what they want to be, especially about hairstyle. Hair is crown for the people head that?s why barbershop offer today's progressive gentlemen a haven where he can sit back, relax and experience the